Liminal Landscapes. The Conception of Nature in Border Territories - Cervera Molina, Ana Elvira (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This text addresses the relationship between literature, philosophy, history and geography, focusing on a very particular element: the landscape. This through the analysis of its representation and enunciation in the liminal scenarios located southeast of New Spain from three narrations of travelers who toured the area between the late seventeenth and early nineteenth centuries. This with the purpose of understanding what is the conception of nature that prevailed over them in relation to the three theses of the Gorgian thought. From this analysis it is argued that in the conception of nature, nothingness and non-being are, from the idea of emptiness, potentially more creative elements for narrating the landscape than the whole and being seen from space which serves as the setting for the action of man.